Production of crude cellulase from Aspergillus versicolor under solid state fermentation (SSF) using different agro waste as substrate - Noorashikin, Johari (Universiti Malaysia Sarawak (UNIMAS), 2015)
Malaysia produced abundant amount of plant waste residues from manufacturing and plantation industry. Sago hampas, rice husk and empty fruit bunch are the examples of agro wastes and they have many beneficial uses in bio based productions. The purpose of this study is to produce cellulase from Aspergillus versicolor (A. versicolor) under solid state fermentation by using three different agro-wastes as substrates which are sago hampas, rice husk and oil palm empty fruit bunch. Fungi are progressively used by the researchers to produce beneficial enzymes like cellulase, pectinase as well as xylanase. Activity of crude cellulase produced was determined by using Filter-paperase activity test (FPase) and DNS method by Miller (1959). Protein determination also was done using Bradford's method to determine the specific cellulase activity. SSF parameters such as initial moisture content, time of incubation, and temperature were optimised in order to produce high enzyme activity of cellulase. Optimum condition for the sago hampas to produce highest cellulase activity (U/ml) is on fourth day of incubation time, 70% of initial moisture content and 30°C of temperature; whereas, both cellulase activities (Ulml) in empty fruit bunch and rice husk substrates was optimum in sixth day of incubation time, with equal 70% of initial moisture content and also 30°C temperature. Hence, based on this study, sago hampas was found to be the best substrate for cellulase production from Aspergillus versicolor.